1990
DOI: 10.1007/bf01344313
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic diversity in epibiotic microflora associated with the Pompeii wormsAlvinella pompejana andA. caudata (Polychaetae: Annelida) from deep-sea hydrothermal vents

Abstract: Abstract. Specimens of alvinellid polychaetes (Alvinella pompejana Desbruy6res andLaubier, 1980 and A. caudata Desbruy6res andLaubier, 1986) and their tubes were sampled from deep-sea hydrothermal vents at 13°N from the manned submersible "Nautile" during the "Hydronaut" cruise (October to November 1987) on the East Pacific Rise. Samples were subjected to bacterial analysis aboard the mother ship "Nadir" to detect bacteria involved in the nitrogen and sulphur cycles, in non-specific heterotrophic processes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…It is important to note that the guts of the lower level consumers (the prey items) are likely to contain ingested free-living bacteria, and their external body surfaces probably host free-living chemoautotrophic bacteria colonists. For example, alvinellids have been shown to possess a dense and diverse assemblage of external bacteria (Prieur et al, 1990), and dense bacterial growth has been observed on the shells of some gastropods such as Depressigyra globulus (C.R.F. and I.A.U.…”
Section: Predatorsmentioning
confidence: 99%
“…It is important to note that the guts of the lower level consumers (the prey items) are likely to contain ingested free-living bacteria, and their external body surfaces probably host free-living chemoautotrophic bacteria colonists. For example, alvinellids have been shown to possess a dense and diverse assemblage of external bacteria (Prieur et al, 1990), and dense bacterial growth has been observed on the shells of some gastropods such as Depressigyra globulus (C.R.F. and I.A.U.…”
Section: Predatorsmentioning
confidence: 99%
“…Despite the great interest of scientists in studying thermophilic or hyperthermophilic micro-organisms, it is generally admitted that mesophiles, as well as moderate thermophiles, may represent the most abundant microbes in hydrothermal vents (Campbell et al, 2001;Jeanthon, 2000). This is exemplified by the isolation of (i) metabolically diverse non-filamentous mesophilic bacteria from the dorsal integument of Alvinella pompejana (Prieur & Jeanthon, 1987;Prieur et al, 1990;Raguénès et al, 1996), (ii) several mesophilic sulfur-oxidizing bacteria (Durand et al, 1993;Jannasch et al, 1985;Ruby & Jannasch, 1982;Wirsen et al, 1998) and (iii) moderate thermophiles belonging to the e-Proteobacteria (Campbell et al, 2001). Sulfate reduction activity was evident in sediments from Guaymas Basin (Elsgaard et al, 1994;Jørgensen et al, 1992) and successful isolation was achieved from various samples collected at different marine hydrothermal environments, thus suggesting the probable ecological significance of SRB in the biogeochemistry of such environments.…”
Section: Strain Am13mentioning
confidence: 99%
“…Various types of bacteria have been cultured, including heavy metal-resistant strains and both heterotrophic and chemolithautotrophic members of the epsilon Proteobacteria (11,31,37,42,43). None of these isolates are the dominant episymbionts, and they represent Ͻ1% of the community (11; B. Campbell and S. Cary, unpublished data).…”
mentioning
confidence: 99%